IDE JAMALUDDIN AL-AFGHANI, MUHAMMAD ABDUH DAN RASYID RIDHA TENTANG NEGARA DAN PEMERINTAHAN DALAM ISLAM - J. Suyuthi Pulungan (Fakultas Adab dan Humaniora UIN Raden Fatah, 2013)
Abstract Emergence of ideas, ideas or thoughts on the state and government in Islam is initiated by Jamalauddin al-Afghani, Muhammad Abduh and Rashid Rida, a thesis and anti-thesis of the condition of the Muslim world in their day. Their thinking is influenced by the Quran, the Islamic government that conditions deteriorated and cultural contacts with the Western world that is progressing. These three figures are contemporary and have a scientific relationship, between teachers and students, do not have the same thoughts that they offer about state and government in Islam. This article discusses the similarities and differences of thought of three figures on the state and government. Keywords: Ideas, People, State, Government and Islam